2012
DOI: 10.1111/j.1468-3083.2012.04582.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and exacerbation of psoriasis with Interferon‐alpha therapy for hepatitis C: A review and analysis of 36 cases

Abstract: Background Interferon-alpha (IFN-α) therapy is used to treat hepatitis C infection. The exacerbation and occurrence of psoriasis in hepatitis C patients treated with IFN-α is increasingly recognized, but the distinct associated features, etiology, and management have not been reviewed. Objective To review all published cases of hepatitis C patients who developed psoriasis while receiving IFN-α therapy. Methods The review was conducted by searching the PubMed database using the keywords “hepatitis C” AND “p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 83 publications
1
52
0
2
Order By: Relevance
“…Furthermore, for this whereas, in the current study only four weekly doses were given for a total period of 1 month. Moreover, IFN is mainly involved in causing Th1 autoimmune diseases such as psoriasis and lichen planus rather than Th2 autoimmune disorders [1,18]. Furthermore, the concomitantly given immunosuppressive therapy would offer a safety belt against the occurrence of such a remote complication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for this whereas, in the current study only four weekly doses were given for a total period of 1 month. Moreover, IFN is mainly involved in causing Th1 autoimmune diseases such as psoriasis and lichen planus rather than Th2 autoimmune disorders [1,18]. Furthermore, the concomitantly given immunosuppressive therapy would offer a safety belt against the occurrence of such a remote complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although correlative evidence from human studies (Afshar et al, 2013, Tas and Atsu, 2015, Kolb-Maurer et al, 2015, Baechler et al, 2006) and results obtained in human psoriatic skin grafted onto immunocompromised mice (Nestle et al, 2005) suggested the role of IFN in psoriatic inflammation, the mechanistic importance of IFN signaling remained controversial based on variable strength of attenuation of the imiquimod-induced inflammation in Ifnar1 -null mice (Grine et al, 2015, Wohn et al, 2013). The latter phenotype might have been underestimated because it was compared with wild type mice where wild type IFNAR1 can undergo accelerated inflammation-induced ubiquitination and downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest the importance of IFN in the pathogenesis of psoriasis. First, iatrogenic development or exacerbation of psoriasis associated with the use of pharmacologic IFN was reported in patients who received IFN to treat hepatitis C, multiple sclerosis, or malignant melanoma (Afshar et al, 2013, Tas and Atsu, 2015, Kolb-Maurer et al, 2015). Second, induction of the IFN-stimulated gene expression signature has been described in samples from psoriasis patients (Baechler et al, 2006, Kim and Krueger, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is an upregulation of type I IFN-inducible genes or genes containing IFN-sensitive response elements (ISREs) found in tissues such as skin lesions in psoriasis and the inflamed joints of rheumatoid arthritis patients (16)(17)(18)(19). Similarly, treatment of patients affected by hepatitis C or multiple sclerosis with IFN-a or IFN-b, respectively, is associated with induction or exacerbation of psoriasis, indicating that type I IFNs can be involved in the pathogenesis of psoriasis (20)(21)(22). Paradoxically, TNF-blocking agents can also induce cutaneous psoriasis-like lesions in patients treated for other autoimmune disorders.…”
mentioning
confidence: 99%